COMPARISON OF INTRAOPERATIVE BLOOD LOSS BETWEEN LIGASURE AND DISSECTION METHOD TONSILLECTOMY (The Research of Medical Science Review, 2025)
Objective: To compare intraoperative blood loss between the LigaSure vessel sealing system and the dissection method of tonsillectomy Method: This comparative cross-sectional study included 60 patients (4-40 years) undergoing elective bilateral tonsillectomy for recurrent tonsillitis and/or tonsillar hypertrophy causing sleep disturbance or dysphagia. Intraoperative blood loss was compared between the LigaSure (n=30) and dissection methods (n=30). SPSS version 25 was used for the data analysis. Age, sex, and surgical indications were also analyzed for their association with blood loss. Results: The median blood loss in the dissection group was 60.0 mL, compared to 6.5 mL in the LigaSure group. The Mann-Whitney U test revealed a significant difference (p=0.000). The mean blood loss for the Dissection group was 69.8 mL, while the LigaSure group had a mean of 13.4 mL. An independent t-test showed a statistically significant difference between the means (p=0.001). Age, sex, and indications for surgery were not significantly correlated with blood loss in this study. Conclusion: The LigaSure vessel sealing system causes significantly less intraoperative bleeding than the dissection method.